Electrochemically Exfoliated High-Quality 2H-MoS2 for Multiflake Thin Film Flexible Biosensors - Zhang, Panpan; Yang, Sheng; Pineda-Gomez, Roberto; Ibarlucea, Bergoi; Ma, Ji; Lohe, Martin R.; Akbar, Teuku Fawzul; Baraban, Larysa; Cuniberti, Gianaurelio (Giovanni); Feng, Xinliang (Small, 2019)
2D molybdenum disulfide (MoS2) gives a new inspiration for the field of nanoelectronics, photovoltaics, and sensorics. However, the most common processing technology, e.g., liquid-phase based scalable exfoliation used for device fabrication, leads to the number of shortcomings that impede their large area production and integration. Major challenges are associated with the small size and low concentration of MoS2 flakes, as well as insufficient control over their physical properties, e.g., internal heterogeneity of the metallic and semiconducting phases. Here it is demonstrated that large semiconducting MoS2 sheets (with dimensions up to 50 µm) can be obtained by a facile cathodic exfoliation approach in nonaqueous electrolyte. The synthetic process avoids surface oxidation thus preserving the MoS2 sheets with intact crystalline structure. It is further demonstrated at the proof-of-concept level, a solution-processed large area (60 × 60 µm) flexible Ebola biosensor, based on a MoS2 thin film (6 µm thickness) fabricated via restacking of the multiple flakes on the polyimide substrate. The experimental results reveal a low detection limit (in femtomolar–picomolar range) of the fabricated sensor devices. The presented exfoliation method opens up new opportunities for fabrication of large arrays of multifunctional biomedical devices based on novel 2D materials.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Ebola biosensors; electrochemical exfoliations; flexible film; molybdenum disulfide